Co‐occurrence of herbivorous fish functional groups correlates with enhanced coral reef benthic state. Issue 3 (25th January 2023) - Sheppard, Catherine E.; Williams, Gareth J.; Exton, Dan A.; Keith, Sally A.
Abstract: Aim: Biodiversity loss is impacting essential ecosystem functions and services across the globe. Recently, our interest in the benefits of biodiversity for ecosystem function has shifted focus from measurements of species richness to functional diversity and composition. However, the additional importance of other community characteristics, such as species evenness and co‐occurrence, for diversity‐driven ecosystem function is less known. We used herbivorous coral reef fish as a model system to investigate how co‐occurrence of different functional groups, rather than purely functional diversity, within an assemblage might affect the coral reef benthic state. Location: Western Atlantic. Time period: 2007–2017. Major taxa studied: Herbivorous reef fish. Methods: We analysed benthic and fish assemblage data from 601 sites across 12 countries in the western Atlantic. Using diversity–interaction models, we investigated how the composition and relative abundances of reef fish functional groups were correlated with benthic cover and estimates of coral calcification rates. We used statistical interactions to explore the importance of co‐occurrence of herbivorous fish functional groups for the coral reef benthic state. Results: We found that co‐occurrence of herbivorous fish functional groups, in addition to functional diversity, was correlated with reduced algal cover and increased coral accretion. Moreover, pairwise statistical interactions between functional groups were significantly correlated with an improvement in the coral reef benthic state. Main conclusions: Our results support the idea that functional group co‐occurrence, in addition to functional diversity, within herbivorous fish offers additional benefits to the coral reef benthic state. We identify farming damselfish and excavating parrotfish as potential key determinants of the coral reef benthic state and highlight that co‐occurrence of cropping and scraping herbivores might promote coral accretion. Our findings support the argument that protecting herbivore abundance without regard to the species and functional groups present is not enough to preserve coral reef health and that fine‐scale community composition must be considered.